2013
DOI: 10.1080/02640414.2013.823223
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive passion: a dependency associated with injury-related risky behaviour in dancers

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 33 publications
4
25
0
1
Order By: Relevance
“…Whereas OP had positive and statistically significant effects on EA, HP had, albeit to a lesser extent, negative and statistically significant effects on EA. This is in line with previous research (Akehurst & Oliver, 2014; Paradis et al., 2013) and DMP (Vallerand, 2010, 2015). Thus, the results of this study show that introjected regulation positively predicted EA not only directly, but also through the mediating role of OP.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Whereas OP had positive and statistically significant effects on EA, HP had, albeit to a lesser extent, negative and statistically significant effects on EA. This is in line with previous research (Akehurst & Oliver, 2014; Paradis et al., 2013) and DMP (Vallerand, 2010, 2015). Thus, the results of this study show that introjected regulation positively predicted EA not only directly, but also through the mediating role of OP.…”
Section: Discussionsupporting
confidence: 94%
“…Additionally, EA has been associated with physical (e.g., risky behaviors, herniated disks, and fascitis) and social (e.g., interpersonal conflicts) negative consequences (Akehurst & Oliver, 2014; Schreiber & Hausenblas, 2015). Research estimates that the prevalence of EA in the general population is around 3%–5%, although this figure may be higher in specific populations, such as sport science students and long-distance runners (Sicilia & González-Cutre, 2011; Symons Downs, Hausenblas, & Nigg, 2004; Szabo, De la Vega, Ruiz-Barquín, & Rivera, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While harmonious passion typically predicts adaptive outcomes (e.g., vitality, life satisfaction), some studies have failed to substantiate these effects (e.g., Mageau et al 2005;Stenseng et al 2011). Moreover, in contrast to the dualistic model, there have been instances in which harmonious passion has had small positive correlations with maladaptive outcomes (e.g., negative affect, exercise dependence; Akehurst and Oliver 2014;Martin and Horn 2013). Equivocal findings have also been documented for obsessive passion.…”
Section: Moderation Of the Passion-outcome Relationshipsmentioning
confidence: 82%
“…The first was Akehurst and Oliver (2014), who concluded that the three needs of autonomy, competence, and relatedness jointly, but not independently, predicted both HP and OP. The first was Akehurst and Oliver (2014), who concluded that the three needs of autonomy, competence, and relatedness jointly, but not independently, predicted both HP and OP.…”
Section: On Passion and Need Satisfactionmentioning
confidence: 99%